GE_GERICHTE P/6384/2020 vom 16. März 2021 - GE Cour de justice (2021)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;DISPOSITIF MEDICATION FORCEE;MESURE THÉRAPEUTIQUE INSTITUTIONNELLE | CPP.81; CPP.310; CPP.130; CP.59